An unusual type of mounting after cephalic duodenopancreatectomy: Temporary external drainage of bile - Mérola, Lorenzo (Cirugía del Uruguay, 1975)
A pancreato-duodenectomy was performed upon a patient with a duodenal cancer, in whom the common bile duct was found to be non-dilated and very thin. The problem of bilio-jejunal anastomosis was solved by closing the choledochus by suture and performing a latero-terminal cholecystojejunostomy. A transient cholecystostomy tube was also left for the externa! drainage of bile, which, added to the aspiration by nasogastric tube, enabled the complete rest of the diverticular jejunal loop, thus favouring a good evolution of the sutures. This technique is recommended for similar situations, provided the accessory biliary ducts are viable.